2019
DOI: 10.1016/j.jds.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of caffeic acid phenethyl ester on alveolar bone loss in rats with endotoxin-induced periodontitis

Abstract: Background/purposeCaffeic acid phenethyl ester (CAPE) is an antioxidant which is decreases the bone resorption and enhances the bone healing. The aim of this study was to investigate the effects of administering systemic CAPE on alveolar bone loss in rats with experimental periodontitis.Materials and methodsThirty male Sprague Dawley rats were divided into three groups: control, endotoxin-induced periodontitis (EP), and EP treated with CAPE (EP-CAPE). Endotoxin was injected into the gingiva of test rats on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…This result may be associated with the anti-osteoclastic effect of CAPE by suppressing RANKL-induced osteoclastogenesis, thereby inhibiting follicular bone loss. As a result, these findings confirmed that CAPE [ 110 , 112 , 113 ] improves bone healing, prevents RANKL-induced osteoclastogenesis, and can be used as a regenerative agent in bone resorption therapy.…”
Section: Biological Propertiessupporting
confidence: 68%
See 1 more Smart Citation
“…This result may be associated with the anti-osteoclastic effect of CAPE by suppressing RANKL-induced osteoclastogenesis, thereby inhibiting follicular bone loss. As a result, these findings confirmed that CAPE [ 110 , 112 , 113 ] improves bone healing, prevents RANKL-induced osteoclastogenesis, and can be used as a regenerative agent in bone resorption therapy.…”
Section: Biological Propertiessupporting
confidence: 68%
“…To analyze follicular bone loss, RANKL activation was evaluated. Histological analyzes revealed lower RANKL levels in the CAPE treated group than in the saline group [ 110 , 111 ]. This result may be associated with the anti-osteoclastic effect of CAPE by suppressing RANKL-induced osteoclastogenesis, thereby inhibiting follicular bone loss.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…injection Positive control: n.a. ↓ RANKL-positive osteoclasts, IL-1β, OSI, alveolar bone loss and histological analysis score with lesser inflammatory reactions, ulcer and hyperemia compared with negative control with diabetes and periodontitis Kizildag et al 43 Animals: 30 male Sprague Dawley rats (3-month old and weight 220−250 g) Mode of disease induction: Endotoxin-induced periodontitis by injecting 10 μL of LPS (1 mg/mL) into the vestibular gingival sites between the right first and second maxillary molars Treatment: i.p. administration of 10 mmol/kg/day CAPE for 28 days after the periodontitis induction Negative control: Saline injection into the vestibular gingival site and daily saline i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were in vitro experiments using mouse bone marrow macrophages (BMMs), RAW264.7, RAW D and MG63 osteoblast cell lines [35][36][37][38][39][40][41] while 19 studies were in vivo studies using Sprague Dawley/ Sprague Dawley albino rats, Wistar/Wistar albino rats, Balb/c mice, lipopolysaccharide (LPS)-resistant C3H/HEJ mice, C57BL/6J mice and ICR mice. 35,38,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] No human studies on this topic were reported.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation